"They all still look the same to me": Navon processing and the cross-race effect. Issue 8 (17th November 2019) - Howard, Simon; Thomas, Ayanna K.; Sommers, Samuel R.
ABSTRACT: Research suggests the Cross-Race Effect (CRE), the difficulty to remember faces from a different race relative to their own, is due to other race faces being processed featurally. It has been theorised that if individuals process other race faces the same as they do same race faces (globally) the CRE could be attenuated. Research inducing global processing, through the use of a Navon processing task, has improved memory for same race faces. Across two experiments we explored if inducing global processing through the Navon processing task prior to encoding (Experiment 1) and at both encoding and retrieval (Experiment 2) would reduce the CRE. Results revealed that biasing White participants' processing orientations failed to improve memory for Black faces. Furthermore, in Experiment 2, global processing impaired participants' memory for identifying faces relative to a control group. Practical implications and the need to address inconsistencies in the Navon processing literature are discussed.